Solusi Terhadap Masalah Sosial Ekonomi Untuk Penjual Nasi Rumahan Yang Terdampak Pandemi Covid-19 - Muhammad Iqbal; Husni Thamrin (Yayasan Literasi Sains Indonesia, 2022)
A pandemic is a disease outbreak that appears simultaneously in various places. WHO said that a pandemic is a term used when an increase in disease transmission and the spread of a virus occurs suddenly and spreads in various countries and can affect many people. not only disturbing health, but also impacting the economic order of all countries. The impact of the pandemic on the economy can lead to low investor sentiment towards the market, which ultimately turns the market in a negative direction. It was also mentioned that the pandemic made economic growth slow down. This was triggered by the policy of social restrictions and regional quarantine. So that economic activity becomes hampered. The pandemic that has occurred since March 2020 has caused the economy to plummet that year. This can be seen from the growth of Gross Domestic Product (GDP) which was recorded -2.07% in 2020. In the previous year GDP still grew up to 5.02%. Not only the world economy experienced a decline, but also small traders felt it. a resident of the city of Tebing Tinggi who is a home-cooked rice seller who feels the impact of the covid-19 pandemic. To increase his income, the home-cooked rice seller also needs a solution, where the practitioner also provides a solution that will be offered. The stage used is the intervention stage at the micro level namely the stage of case work from Skidmore Thackeray and Farley in Adi (2005: 149) which consists of the research stage, the assessment stage, the intervention stage, and the termination stage.